A critical period for paired-housing-dependent autistic-like behaviors attenuation in a prenatal valproic acid-induced male mouse model of autism - Yang, Jian-Quan; Yin, Bao-Qi; Yang, Chao-Hua; Jiang, Miao-Miao; Li, Zhe (Frontiers in Neuroscience, 2025)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by impairments in social communication and the presence of restrictive and repetitive behaviors. Investigating the etiological process and identifying an appropriate therapeutic target remain as formidable challenges to overcome ASD due to numerous risk factors and complex symptoms associated with the disorder. Recent studies have indicated that early rehabilitative intervention can alleviate the symptoms of individuals with ASD. However, there remain unsolved issues of behavioral intervention such as the appropriate time and types of therapies. In this study, we employed a mouse model prenatally exposed to valproic acid to establish a validated ASD mouse model and We found that paired-housing with control mice for 4 week after weaning palliated sociability deficits, anxiety and repetitive behaviors in this model of ASD-like behaviors, while paired-housing with their ASD littermate did not produce this effects. Furthermore, by evaluating different time window of paired-housing, we found that paired-housing during postnatal day 21 (P21) to P35, but not P21 to P28 or P35 to P49 or P28 to P35, is a critical period for the influence of paired-housing on autistic-like behaviors. Finally, paired-housing with control mice improved the impaired GABA system in this model of ASD. So our study demonstrates the therapeutic potential of environmental intervention during a critical period in the treatment of ASD.